IMPLEMENTATION OF MULTICULTURAL IDEAS IN THE EDUCATIONAL SPACE OF HIGHER EDUCATIONAL ESTABLISHMENTS - Chervinska, Inna; Derevianko, Oksana; Chervinskyi, Andrii; Haliuk, Nadia (Mountain School of Ukrainian Carpaty, 2021)
The article emphasizes that the study of processes and phenomena that occur in the modern educational and cultural space are the most important pedagogical and cultural issues. The authors point out that the globalization processes which take place in the modern world community determine the formation of new systemic phenomena and events in society. Such innovative phenomena in the educational space include multicultural education, which since the beginning of the XXI century has acquired special significance becoming one of the priority trends in the cultural and educational development of civilization. It is noted that the leading ideas of multiculturalism become especially relevant and important for the educational community in connection with the developent of migration processes, urbanization and border expansion. Therefore, for a young person, the knowledge of several languages, history and culture of other nations is urgent, as it characterizes their role in society and determines their place in the educational space. The purpose of the article is to reveal the specifics of the implementation of the ideas of multiculturalism in the modern educational space of higher educational establishments on the basis of a profound content analysis of the scientific literature, the study of practical experience of higher educational establishments. The authors state that the multicultural component of the educational space of the higher educational establishments is determined by the mutual influence of many cultural components, the direct carriers of which are students from different regions of Ukraine and abroad. Under these circumstances, the importance of multicultural education and upbringing in the formation of young people is increasing. Depending on historical, political, socio-cultural factors, the components of the educational space, the educational and cultural traditions of a region, various models of multicultural education are built, which determine the priorities of readiness of a growing individual to live in a multicultural society.